Tools to Assess the Trustworthiness of Evidence-Based Point-of-Care Information for Health Care Professionals: Systematic Review - Lenaerts, Gerlinde; Bekkering, Geertruida E; Goossens, Martine; De Coninck, Leen; Delvaux, Nicolas; Cordyn, Sam; Adriaenssens, Jef; Vankrunkelsven, Patrick (JMIR Publications, 2020)
BackgroundUser-friendly information at the point of care should be well structured, rapidly accessible, and comprehensive. Also, this information should be trustworthy, as it will be used by health care practitioners to practice evidence-based medicine. Therefore, a standard, validated tool to evaluate the trustworthiness of such point-of-care information resources is needed. ObjectiveThis systematic review sought to search for tools to assess the trustworthiness of point-of-care resources and to describe and analyze the content of these tools. MethodsA systematic search was performed on three sources: (1) we searched online for initiatives that worked off of the trustworthiness of medical information; (2) we searched Medline (PubMed) until June 2019 for relevant literature; and (3) we scanned reference lists and lists of citing papers via Web of Science for each retrieved paper. We included all studies, reports, websites, or methodologies that reported on tools that assessed the trustworthiness of medical information for professionals. From the selected studies, we extracted information on the general characteristics of the tools. As no standard, risk-of-bias assessment instruments are available for these types of studies, we described how each tool was developed, including any assessments on reliability and validity. We analyzed the criteria used in the different tools and divided them into five categories: (1) author-related information; (2) evidence-based methodology; (3) website quality; (4) website design and usability; and (5) website interactivity. The percentage of tools in compliance with these categories and the different criteria were calculated. ResultsIncluded in this review was a total of 17 tools, all published between 1997 and 2018. The tools were developed for different purposes, from a general quality assessment of medical information to very detailed analyses, all specifically for point-of-care resources. However, the development process of the tools was poorly described. Overall, seven tools had a scoring system implemented, two were assessed for reliability only, and two other tools were assessed for both validity and reliability. The content analysis showed that all the tools assessed criteria related to an evidence-based methodology: 82% of the tools assessed author-related information, 71% assessed criteria related to website quality, 71% assessed criteria related to website design and usability, and 47% of the tools assessed criteria related to website interactivity. There was significant variability in criteria used, as some were very detailed while others were more broadly defined. ConclusionsThe 17 included tools encompass a variety of items important for the assessment of the trustworthiness of point-of-care information. Overall, two tools were assessed for both reliability and validity, but they lacked some essential criteria for the assessment of the trustworthiness of medical information for use at the point-of-care. Currently, a standard, validated tool does not exist. The results of this review may contribute to the development of such an instrument, which may enhance the quality of point-of-care information in the long term. Trial RegistrationPROSPERO CRD42019122565; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=122565